Biodosimetry, can it find its way to the nuclear medicine clinic? - Bolcaen, Julie; Combrink, Nastassja; Spoormans, Kaat; More, Stuart; Vandevoorde, Charlot; Fisher, Randall; Kleynhans, Janke (Frontiers in Nuclear Medicine, 2023)
Personalised dosimetry based on molecular imaging is a field that has grown exponentially in the last decade due to the increasing success of Radioligand Therapy (RLT). Despite advances in imaging-based 3D dose estimation, the administered dose of a therapeutic radiopharmaceutical for RLT is often non-personalised, with standardised dose regimens administered every 4–6 weeks. Biodosimetry markers, such as chromosomal aberrations, could be used alongside image-based dosimetry as a tool for individualised dose estimation to further understand normal tissue toxicity and refine the administered dose. In this review we give an overview of biodosimetry markers that are used for blood dose estimation, followed by an overview of their current results when applied in RLT patients. Finally, an in-depth discussion will provide a perspective on the potential for the use of biodosimetry in the nuclear medicine clinic.